2014
DOI: 10.1089/scd.2013.0182
|View full text |Cite
|
Sign up to set email alerts
|

Mouse-Induced Pluripotent Stem Cells Generated Under Hypoxic Conditions in the Absence of Viral Infection and Oncogenic Factors and Used for Ischemic Stroke Therapy

Abstract: Induced pluripotent stem (iPS) cells are considered as having the greatest potential for use in cell-based therapies. However, at least two hurdles remain: integrating viral transgenes and introducing the c-Myc and Klf4 oncogenes. In a previous study, fibroblasts were incapable of generating iPS cells in the absence of both oncogenes and viral infection. For the present study, we tested our hypothesis that iPS cells can be generated without oncogenes and viral infection under hypoxic conditions and used for ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Recently, a novel strategy was reported that using a combination of Oct4 and Sox2 plasmid transfection with hypoxia conditioning to generate iPS cells (iPS-OSH cells). iPS-OSH-derived NPCs differentiated into neurons and astrocytes after being injected into ischemic mice brain, accompanied by improved neurobehavioral recovery [45].…”
Section: Induced Pluripotent Stem Cells (Ips)mentioning
confidence: 99%
“…Recently, a novel strategy was reported that using a combination of Oct4 and Sox2 plasmid transfection with hypoxia conditioning to generate iPS cells (iPS-OSH cells). iPS-OSH-derived NPCs differentiated into neurons and astrocytes after being injected into ischemic mice brain, accompanied by improved neurobehavioral recovery [45].…”
Section: Induced Pluripotent Stem Cells (Ips)mentioning
confidence: 99%
“…By targeting the subacute and chronic phases of stroke, stem cells significantly extend the effective period of intervention, permitting a larger patient population to benefit from this prospective treatment. From the many cell types which have been transplanted in the laboratory, a small fraction have reached clinical trials for cell therapy in stroke, including fetal cells, NT2N cells, CTX0E3, embryonic stem cells, neural stem/progenitor cells, umbilical cord blood, amnion, adipose, and induced pluripotent stem cells [6], [7], [8], [9], [10]. Bone marrow-derived cells have been distinguished in preclinical studies and ongoing clinical trials largely due to maintaining a consistent safety profile when used in other diseases [11], [12].…”
Section: Stem Cell Biology and Therapymentioning
confidence: 99%
“…From the initial study of fetal cell transplantation into stroke animals, varying levels of histological and behavioral recovery have been demonstrated in NT2N, CTX0E3, embryonic stem cells, hematopoietic stem cells, neural stem cells, adult tissue-derived stem cells, and induced pluripotent stem cells [711, 22]. The quest for the optimal cell type for transplantation therapy has largely been dictated by ethical and logistical issues [23, 24].…”
Section: So Many Choices But We Need To Identify the Best Stem Cellmentioning
confidence: 99%